Distribution and frequency of Culex pipiens and Culex torrentium (Culicidae) in Europe and diagnostic allozyme markers. Issue 29 (2011) - Weitzel, Thomas; Braun, Kathrin; Collado, Amandine; Jöst, Artur; Becker, Norbert
No abstract available